The Role of CEO Altruism in Moderating the Relationship between Affective Commitment and Integrity with OCB in Culinary SMES - Siddiq, Dedi; Mukhibulloh, Mukhibulloh; Dewi, Annah; Astuti, Ramlah; Alang, Tho (International Research Journal of Business Studies, 2024)
This research aims to examine the relationship between chief executive officer (CEO) altruism, affective commitment, integrity and organizational citizenship behavior (OCB). More specifically, this research examines the extent to which the role of CEO altruism plays in moderating the relationship between employee affective commitment and integrity towards employee OCB of small and medium businesses in the culinary sector in Indonesia. This research uses quantitative approach and data were collected through paper-based survey. Data analysis uses multiple regression and moderated regression analysis with a significant level of 0.05 to test the hypothesis. The research found that employee affective commitment and integrity have a positive effect on OCB. In addition, CEO altruism plays a significant role as a moderating variable in strengthening the relationship between employee affective commitment and OCB and also strengthening the relationship between employee integrity and OCB. These findings provide important insights for SME managers to demonstrate altruism towards their employees so as to increase employee OCB.